Epidemiology of children's swimming competence and water safety - Asier Santibañez-Gutierrez; Julen Fernández-Landa; Julio Calleja-González; Nikola Todorović; Marijana Ranisavljev; Valdemar Štajer; Bogdan Anđelić; Nataša Zenić; Antonino Bianco; Patrik Drid (Frontiers Media S.A., 2022)
IntroductionThe main purpose of this study was to investigate children's swimming competence in primary schools of districts in Vojvodina, Serbia.MethodsIncluded subjects were primary school students from first to eighth grade (N = 2,778; male = 1,454, female = 1,324; age = 10.73 ± 2.1 years). We used Swimming Competence Questionnaire to acquire and analyze their swimming experience, non-fatal aquatic events, and demographics. For the statistical analysis, logistic regression and hierarchical multiple regression were used to evaluate if the factors and SC and NFAE were associated. The analyses were carried out by using SPSS® software version 24.0 (SPSS, Inc., Chicago, Illinois, USA).ResultsFamilies with more income and education generally have children with more swimming competence, experience, knowledge, and skills related to water safety. First step in analysis revealed that gender (β = 0.05, p < 0.01), education level (β = 0.06, p < 0.01) age (β = 0.171, p < 0.01), and family income (β = 0.04, p < 0.01) were significant swimming competence (SC) predictors (R2 = 0.04). Age (OR = 1.15, p < 0.01) was the only significant predictor in Step 1 predicting non-fatal aquatic events (NFAE). In Step 2, variables associated with SC were swimming location (ΔR2 = 0.06, p < 0.01), swimming experience (ΔR2 = 0.16, p < 0.01), swimming accessibility (ΔR2 = 0.05, p < 0.01), and learning experience (ΔR2 = 0.03, p < 0.01) (total R2 = 0.26 to 0.47, p < 0.01). Only a minority of participants reported that they could not swim further than 5 meters using general stroke (37.15%).ConclusionNational education trainers programs must be prioritized with the primary strategy of transferring knowledge to swimming and water safety. Families with lower income must be included without exceptions. This is perhaps a key factor in preventing NFAE, increasing SC, and increasing water safety.